On-Site Disposal and Burial of Pit Wastes (Two Southern Iraqi Oil Fields) - Al-Haleem, Ayad; Saeed, Essam; Abdulwahab, Dhiya (Iraqi Journal of Science, 2023)
On-site pit is the most common option that may be used to dispose drilling wastes. The contents of these pits vary, depending on the lithology of formations drilled and the drilling mud ,and different chemical additives.Eighty samples of mud (sludge) and eighty samples of water have been collected from ten pits of two Iraqi oilfields(North Rumaila and South Rumaila/southern Iraq) and were chemically analyzed for metals Cr, Pb,As, Zn, Fe, Mn,K , Na,Ba, Ca, Mg,SO4=,and Cl- in order to determine the quality and quantity content of studied reserve pitsInefficient equipment, using toxic materials for various drilling processes, absence of regulations for the design and monitoring of pit during and after drilling operation, and leaking and spilling from many rig equipment, these factors contribute and cause a local environmental impact at the drilling sites.This study confirmed the need for an alternative options that known globally instead of earthen pits such as closed-loop drilling systems to manage drilling mud and cuttings .